Determinants of Mental Healthcare-Seeking Behavior of Postpartum Women in Ibadan, Nigeria - Odufuwa, Oyeteju T.; Olaniyan, Olanrewaju; Okuonzi, Sam A. (Frontiers in Global Women's Health, 2022)
Mental healthcare seeking behaviour of postpartum mothers has received little attention in Nigeria. Previous studies in the country have focused on determinants of physical health seeking behavior, choice of maternal healthcare provider, prevalence and determinants of maternal mental illness, yet, determinants of maternal mental health seeking behaviour among Nigerian women has been understudied. This study, therefore examined the determinants of mental health seeking behavior among postpartum women in Ibadan, Nigeria. Maternal mental illness which was proxied using Postpartum Depression, was computed using the Edinburgh Postpartum Depression Scale. Data for the study was obtained through survey method using a 9-page questionnaire. A 3-stage sampling technique was employed. The first stage was a stratified sampling to disaggregate the health facilities offering postnatal and immunization services, on the basis on ownership into public and private healthcare providers. In the second stage, seven healthcare facilities comprising of three (3) private and four (4) public healthcare were purposively selected based on number of attendees. The final stage was a random selection of 390 postpartum mothers attending postnatal and immunization clinics across seven healthcare facilities. The prevalence of depression among the mothers was 20.8%. While only 39.5% of the depressed women sought care, 22.3% of the non-sufferers also sought mental healthcare. This revealed that both sufferers and non-sufferers sought mental healthcare. Also, higher incidence of postpartum depression among the sufferers increased the likelihood of seeking mental healthcare. Age, family history of postpartum depression and having the desired gender of child were determinants of mental healthseeking behavior. Among the sufferers of postpartum depression who failed to seek care, low perceived need for mental healthcare, perception that the depressive symptoms will go on its own, as well as fear of being stigmatized as a ‘weak mother”, were reasons for not seeking mental healthcare. Thus, to promote mental healthcare, the non-cost factors, like availability and accessibility to mental healthcare facility should be addressed. In order to achieve this, mental healthcare sensitization programmes should be integrated into maternal healthcare at all levels; and mothers attending antenatal clinics should be routinely screened for early symptoms of depression in the postpartum period.